Data from: Late Pleistocene origin of the entire circumarctic range of the arctic-alpine plant Kalmia procumbens - Ikeda, Hajime; Eidesen, Pernille Bronken; Yakubov, Valentin; Barkalov, Vyacheslav; Brochmann, Christian; Setoguchi, Hiroaki (Dryad, 2017)
Data-Ikeda-Mol_Ecol The circumarctic ranges of arctic-alpine plants are thought to have been established in the late Pliocene/early Pleistocene, when the modern arctic tundra was formed in response to climate cooling. Previous findings of range-wide genetic structure in arctic-alpine plants have been thought to support this hypothesis, but few studies have explicitly addressed the temporal framework of the genetic structure. Here, we estimated the demographic history of the genetic structure in the circumarctic Kalmia procumbens using sequences of multiple nuclear loci and examined whether its genetic structure reflects prolonged isolation throughout the Pleistocene. Both Bayesian clustering and phylogenetic analyses revealed genetic distinction between alpine and arctic regions, whereas detailed groupings were somewhat discordant between the analyses. By assuming a population grouping based on the phylogenetic analyses, which likely reflects a deeper intraspecific divergence, we conducted model-based analyses and demonstrated that the intraspecific genetic divergence in K. procumbens likely originated during the last glacial period. Thus, there is no need to postulate range separation throughout the Pleistocene to explain the current genetic structure in this species. This study demonstrates that range-wide genetic structure in arctic-alpine plants does not necessarily result from the late Pliocene/early Pleistocene origin of their circumarctic ranges, and emphasizes the importance of a temporal framework of the current genetic structure for understanding the biogeographic history of the arctic flora.